2000
DOI: 10.2527/2000.78123070x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lacha and Rasa Aragonesa lambs slaughtered at three live weights.

Abstract: A study was made of differences in the quality of meat from Lacha (L) and Rasa Aragonesa (RA) lambs slaughtered at 12, 24, or 36 kg live weight. Lambs from both breeds were weaned at 25 to 57 d, approximately 11.5 to 18.5 kg live weight, and fed concentrate and barley straw until slaughter at 24 and 36 kg live weight. Hot carcass weight, cold carcass weight, conformation, color, firmness, and thickness of backfat and color of rectus abdominis muscle were recorded on the carcass. Final pH (pHu), instrumental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
49
7
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 25 publications
18
49
7
6
Order By: Relevance
“…Shear force increased with live weight. The values found were similar to those found by Sañ udo et al (1996); Beriain et al (2000) and Hoffman et al (2003). The lowest values found for the lightest lambs were also found by Schö nfeldt, Naudé, Bok, Van Heerden, and Sowden (1993) for young lambs and kids.…”
Section: Instrumental Measurementssupporting
confidence: 72%
See 2 more Smart Citations
“…Shear force increased with live weight. The values found were similar to those found by Sañ udo et al (1996); Beriain et al (2000) and Hoffman et al (2003). The lowest values found for the lightest lambs were also found by Schö nfeldt, Naudé, Bok, Van Heerden, and Sowden (1993) for young lambs and kids.…”
Section: Instrumental Measurementssupporting
confidence: 72%
“…Live weight had no effect on pH measured 1 h after slaughter, but when the measurement was made 24 h after slaughter the heavy lambs had significantly higher pH values. Sañudo et al (1996) and Beriain et al (2000), working with lambs from Spanish breeds also observed higher pH values on the heavy carcasses but Vergara, Molina, and Gallego (1999) also working with a Spanish breed did not find effects of slaughter weight on 24 h pH. In the present work, no differences were found between breeds for pH measured 24 h after slaughter, but when pH was measured 1 h after slaughter the Mirandesa breed had significantly higher values.…”
Section: Instrumental Measurementscontrasting
confidence: 43%
See 1 more Smart Citation
“…Stoga ne čudi činjenica što se boja janjećega mesa smatra ključnim čimbenikom koji utječe na potrošačev dojam te vrijednost samoga proizvoda (Calnan i sur., 2014.). Vrijednost pH, kao mjera glikolitičkog potencijala, kreće se u rasponu od 6,85 do 6,05 u janjećem trupu 45 minuta nakon klanja (1) ). Međutim, neznatan je broj radova provedenih u Hrvatskoj koji se odnose na pH vrijednost i pokazatelje boje janjećega mesa nakon hlađenja.…”
Section: Uvodunclassified
“…Since the consumer preferences and cuisine traditions are various, the meat flavour is also different according to the slaughter weight (horcaDa et al, 1998;BeriaiN et al, 2000). Lightness decreased with increasing live weight and the light lambs had higher yellow index than the heavier lambs.…”
mentioning
confidence: 99%